Automated Noncontact Ultrasound Imaging and Ablation System for the Treatment of Atrial Fibrillation: Outcomes of the First-in-Human VALUE Trial. (March 2020) - Turagam, Mohit K.; Petru, Jan; Neuzil, Petr; Kakita, Ken; Kralovec, Stepan; Harari, David; Phillips, Patrick; Piazza, Danielo; Whang, William; Dukkipati, Srinivas R.; Reddy, Vivek Y.
Abstract : Background: Catheter ablation for atrial fibrillation (AF) using point-by-point radiofrequency energy or single-application one-shot balloons is either technically challenging or have limited ability to accommodate variable patient anatomy to achieve acute and durable pulmonary vein (PV) isolation. A novel ablation system employs low intensity collimated ultrasound (LICU)-guided anatomic mapping and robotic ablation to isolate PVs. In this first-in-human, single-center, multioperator trial, VALUE trial (VytronUS Ablation System for Treatment of Paroxysmal Atrial Fibrillation; NCT03639597) in patients with paroxysmal atrial fibrillation, this LICU system was evaluated to determine its safety, effectiveness in PV isolation, and freedom from recurrent atrial arrhythmias. Methods: In the enrolled 52 patients with paroxysmal atrial fibrillation, ultrasound M-mode–based left atrial anatomies were successfully created, and ablation was performed under robotic control along an operator-defined lesion path. The LICU system software advanced over the course of the study: the last 13 patients were ablated with enhanced software. Results: Acute PV isolation was achieved in 98% of PVs—using LICU-only in 77.3% (153/198) of PVs and requiring touch-up with a standard radiofrequency ablation catheter in 22.7% (45/198) PVs. The touch-up rate decreased to 5.8% (3/52) in patients undergoing LICU-ablation with enhanced software. Freedom from atrial arrhythmia recurrence was 79.6% (39/49 patients) at 12 months or 92.3% (12/13 patients) with the enhanced software. Major adverse events occurred in 3 patients (5.8%): one had transient diaphragmatic paralysis, one vascular access complication, and one had transient ST-segment elevation from air-embolism, without sequelae. Conclusions: In this first-in-human study, low- intensity collimated ultrasound-guided anatomic mapping and robotic ablation allows PV isolation with good chronic safety; PV isolation success is improving with device enhancements. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03639597. Abstract : Supplemental Digital Content is available in the text.